Isolation and Identification of Gram-Negative Bacteria on Cattle Farms Indicated by Mastitis - Ayuti, Siti Rani; Pratiwi, Zahwa Amelia; Admi, Masda; Darniati, Darniati; Isa, M; Herrialfian, Herrialfian (The Faculty of Veterinary Medicine of Syiah Kuala University, 2022)
Mastitis is oneofthe causesofdiseases that can reduce livestock production.Mastitis can be caused by various types of bacteria that cause a decrease in livestock production that is difficult to cure with antibiotics has been reported resistance. This study aims to determine gram-negative bacteria that can be the cause of mastitis in cows. The study used samples taken from folk farms by means of livestock udder swabs. Bacterial isolation is carried outbyplanting in Mannitol Salt Agar (MSA) mediaandidentifying by Gram stainingandbiochemical tests (maltose and lactose). The data analysis used is descriptive analysis, namely the types of bacteria as the causative agents of mastitis.The results of the study obtained bacteria that cause mastitis ofgram-negative speciesKlebsiellaspandEnterobactersp yang classified as Gram-negativebacteria. It can be concluded that in cows indicated mastitis there are Gram-negative bacteria, these are morphologically identified, namelyKlebsiellaspandEnterobactersp.